2004
DOI: 10.1097/00006416-200409000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Unique Issues in Pediatric Spinal Cord Injury

Abstract: Spinal cord injuries are devastating events, and they are particularly tragic when they affect children or adolescents who have barely had an opportunity to experience life. Of the approximately 10,000 individuals who sustain spinal cord injury each year in the United States, 3% to 5% occur in individuals younger than 15 years of age and approximately 20% occur in those younger than 20 years of age (Nobunaga, Go, & Karunas, 1999). Because of the growth and development inherent in children and adolescents and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…Spasticity is a common impairment in children with spinal cord injury (SCI). Vogel et al reported that approximately 50% of children with SCI exhibit spasticity (2). The management of spasticity in children may be especially critical to prevent long-term orthopedic complications associated with spasticity such as joint contractures and hip dislocation (3).…”
Section: Introductionmentioning
confidence: 99%
“…Spasticity is a common impairment in children with spinal cord injury (SCI). Vogel et al reported that approximately 50% of children with SCI exhibit spasticity (2). The management of spasticity in children may be especially critical to prevent long-term orthopedic complications associated with spasticity such as joint contractures and hip dislocation (3).…”
Section: Introductionmentioning
confidence: 99%
“…SCI in children may also occur in association with birth injuries, skeletal dysplasias, juvenile idiopathic arthritis, and Down syndrome [5].…”
Section: Epidemiologymentioning
confidence: 99%
“…28 Moreover, 60% to 80% of all pediatric vertebral injuries were in the cervical spine, whereas cervical spinal injuries accounted for only 30% to 40% of all adult vertebral injuries. 32 The American Spinal Cord Association (ASIA) classification is widely used for assessing and classifying patients with SCI. 32 The American Spinal Cord Association (ASIA) classification is widely used for assessing and classifying patients with SCI.…”
Section: Spinal Cord Injuries In the Pediatric Populationmentioning
confidence: 99%
“…32,34 In most SCIs, a significant hyperextension and flexion moment exists, resulting from an acceleration/deceleration force that may cause excessive displacement of vertebral structures that can injure the spinal cord. 32,34 In most SCIs, a significant hyperextension and flexion moment exists, resulting from an acceleration/deceleration force that may cause excessive displacement of vertebral structures that can injure the spinal cord.…”
Section: American Spinal Injury Association (Asia) Impairment Scalementioning
confidence: 99%